Effects of icing, prestressing and laminate buckling stresses on the design of guyed towers. Issue 21 (20th October 2021) - Alshurafa, Sami; Rose, Andrew; Polyzois, Dimos
Abstract: The article includes a comprehensive review of the design standards and specifications of ice accumulation used to design guyed structures and transmission lines. Both experimental and theoretical results are included. A total of 25 GFRP coupons were tested to failure to obtain material properties. The effects of icing, cable prestressing and the critical buckling stresses due to the extension and shear modes of failure on the design of multi-cell guyed towers are evaluated and discussed. The article evaluates the critical buckling stresses with reference to the percentage of fiber volume fractions and it provides a method to assess and control the design of guyed towers. Moreover, it provides a non-linear finite element model to analyze and set a design limit by predicting the maximum wind load profile that causes failure of the GFRP jointed guyed tower.